Evidence of exercise-induced muscle damage following a simulated rugby league match - Twist, C.; Sykes, D, (European Journal of Sport Science, 2011)
This study investigated symptoms of exercise-induced muscle damage following a simulated rugby league game. Ten male participants were assessed before, immediately after (0 h), and 24 and 48 h after the simulated game. Perceived muscle soreness was higher at all time points (P=0.001) and creatine kinase values were increased at 24 h following the simulated game (P=0.001). Peak knee extensor torque at 60 deg · s-1 was reduced up to 48 h (P =0.04) but was unchanged at 240 deg · s-1. Similarly, peak knee flexor torque at 60 deg · s-1 was lower than baseline up to 24 h, while at 240 deg · s-1 it was reduced at 24 h only (P=0.045). Correlations between changes in strength loss of the knee extensors and fat mass to fat-free mass ratio reveleaved no significant relationship between variables (P >0.05). In addition, countermovement jump performance was reduced at 0 and 24 h following the simulated game (P=0.008). Our results suggest that symptoms of exercise-induced muscle damage occur up to 48 h following a simulated rugby league match. Coaches should be cognisant of the large increases in muscle soreness and reductions in slow velocity force generation, and should adapt training accordingly in the 48 h period following a game.